2020
DOI: 10.1136/tobaccocontrol-2019-055255
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of tobacco product cessation among youth and adults in the USA: findings from the PATH Study Waves 1–3 (2013–2016)

Abstract: ObjectiveTo report on demographic and tobacco use correlates of cessation behaviours across tobacco products (cigarettes, electronic nicotine delivery systems (ENDS), cigars, hookah and smokeless tobacco) among the US population.DesignData were drawn from the first three waves (2013–2016) of the Population Assessment of Tobacco and Health Study, a nationally representative, longitudinal cohort study of US youth (ages 12–17) and adults (ages 18+) . Past 30-day (P30D) tobacco users at Wave 1 (W1) or Wave 2 (W2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…The main categories included: persistent use (continued use across multiple time points), discontinued use (use to no use), relapse (stopped use and began use again), switching (changing between product types), and inconsistent use (back and forth between use and non-use). Evidence from the PATH Study has shown that the majority of cigarette smokers persist with smoking across time [ 10 , 11 ], whereas transition behaviors among smokers initiating and persisting with NVP use (concurrent users) are more highly variable [ 11 , 12 , 13 ]. Moreover, continuing with/transitioning toward cigarettes, is more common than continuing with/transitioning toward NVPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main categories included: persistent use (continued use across multiple time points), discontinued use (use to no use), relapse (stopped use and began use again), switching (changing between product types), and inconsistent use (back and forth between use and non-use). Evidence from the PATH Study has shown that the majority of cigarette smokers persist with smoking across time [ 10 , 11 ], whereas transition behaviors among smokers initiating and persisting with NVP use (concurrent users) are more highly variable [ 11 , 12 , 13 ]. Moreover, continuing with/transitioning toward cigarettes, is more common than continuing with/transitioning toward NVPs.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to differential transitions away from smoking by vaping status, Coleman et al [ 12 ] found that among baseline concurrent users, daily vapers were more likely than non-daily vapers to report smoking abstinence at follow-up. Kasza et al [ 13 ] found that vaping was positively associated with making attempts to quit, but was not associated with discontinuing smoking among attempters. However, some caution is required when interpreting population-based studies as NVP use is not randomized and there is reason to believe those vaping differ from those who are not.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies can also examine correlates that predict these unique patterns among exclusive and non-exclusive hookah users. Kasza et al 44 45 and Edwards et al 46 examine demographic correlates of initiation, cessation and relapse of hookah use to further explore predictors of these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows that the broad transitions of initiation, cessation and relapse can occur in steps (denoted by showing two arrows between user states); for example, cigarette smoking cessation is composed of moving from being a current smoker to making a quit attempt to succeeding in a quit attempt. Three papers in this issue describe correlates of the broad transitions of initiation,22 cessation23 and relapse24 for each type of tobacco product, along with correlates of steps within each of these transitions over a 1-year time frame using data from W1 to W2 and from W2 to W3 of the PATH Study. Table 2 lists the individual-level initial correlates considered in this issue for each of the broad transitions and steps within them, though other factors at the environment level or product level, for example, may also relate to transition behaviours or interact with individual-level correlates to affect transition behaviours.…”
Section: Overview Of Tobacco Use Transitions For Population Healthmentioning
confidence: 99%
“…Specifically, we outline a high-level conceptual overview to guide thinking about three broad transition behaviours: (1) initiation of tobacco use among non-users; (2) cessation of use among current users; and (3) relapse back to tobacco use among former users. These transition behaviours can apply to several different types of tobacco products4–9 and may be influenced by a set of demographic and tobacco use correlates 22–24. The papers that follow in this journal issue use this overview for different tobacco products among youth 12–17 years of age, young adults 18–24 years of age and adults 25 years of age and older.…”
Section: Introductionmentioning
confidence: 99%